(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The aim of the study was to investigate the effect of teaching activities focused on the inclusive and exclusive definition of quadrilaterals on the associative skills of 7th grade students. The sample of the study consists of 31, 7th grade students; 16 students in the experimental group and 15 students in the control group. The study conducted in a public school in Middle Black Sea Region in Turkey. The design of the study was pre-test - post-test control group week experimental design. As a data collection tool, an achievement test developed by the researchers under the guidance of expert opinion based on the literature. This test used as pre-test and post-test. The study lasted in 5 weeks. Instruction focused on inclusive definition of quadrilaterals in experimental group while exclusive definition of quadrilaterals in control group. T-test analysis was used to find the difference between pre-test and post-test scores via SPSS program. According to findings, there was no statistically significant difference between the pre-test scores of the experimental group and the control group, but there was a statistically significant difference between the test group and the control group in favor of the experimental group at the end. As a result, it can be said that associative instruction has positive effects on student achievement in quadrilaterals.